ARQUITETURA COLONIAL SOB A ÓTICA DA EFICIÊNCIA ENERGÉTICA: O CASO DO MUSEU REGIONAL DE CAETÉ - Felício, Rafaela Alves; Grigoletti, Giane de Campos; Gabriel, Helena Reginato (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This work presents the evaluation of energy efficiency of the Regional Museum of Caeté, a Brazilian historic heritage built in Minas Gerais. Energy evaluation was carried through the application of RTQ-C, Brazilian regulation for energy efficiency of public, offices buildings, using the simulation method with Design Builder software. A bibliographic review and in situ inventories were carried out in order to describe the building system of Caeté Regional Museum, according to its historical technology and constructive techniques. In order to evaluate the energy efficiency through the simulation, the parameters for the configuration of the real model and reference model were analyzed according to the building envelop and artificial light sources. The museum reach the level B for overall classification, since is natural ventilated. For the envelope, the museum reach level E, and level C for artificial light sources. The envelope presents potential for improvement considering the window frames that are formed only by opaque shutters, resulting in opened windows during the workday. Providing better thermal insulation of roof and attach window glass panels, the level became level A for envelope and artificial light sources.